2010
DOI: 10.1063/1.3531597
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to Determinate Pupillary Responses Based in High Speed Videoculography in Clinical Eye Applications

Abstract: The aim of this article is to present the application of high speed videoculography as a tool during the development of a methodology to employ in the ocular clinic diagnostic. It shows exist a significant statistically difference between groups in the time to maximum contraction velocity. And it does not exit a significant statistically difference in the latency and the maximum contraction velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Although the luminance levels used and the age between groups were different, it does not exist a significant statistically difference in latency and maximum contraction velocity ( Figure 14) between groups. At the same time, the results indicated that age and IOL do not affect statistically on them, however, the TPVC, is far from it [45].…”
Section: High-speed Vog Applied In a Comparative Study Between Iol Ansupporting
confidence: 57%
“…Although the luminance levels used and the age between groups were different, it does not exist a significant statistically difference in latency and maximum contraction velocity ( Figure 14) between groups. At the same time, the results indicated that age and IOL do not affect statistically on them, however, the TPVC, is far from it [45].…”
Section: High-speed Vog Applied In a Comparative Study Between Iol Ansupporting
confidence: 57%